The Prior-to-isolation Psychosocial Experiences of COVID-19 Diagnosed Patients: An Interpretive Phenomenological Analysis - Heni Dwi Windarwati; Setyawati Soeharti; Mira Wahyu Kusumawati (Jurnal Keperawatan Padjadjaran, 2022)
Background: Changes that occurred during COVID-19 pandemic have caused people to have various responses when receiving a diagnosis of COVID-19; among others are stigma in society, lack of knowledge, various social media news that aﬀect people’s beliefs, and mental health during the pandemic. Purpose: The purpose of this study was to explore the psychosocial experiences of patients before and when they were frst diagnosed with COVID-19. Methods: Using a phenomenological approach, we involved 19 COVID-19 survivors who were medically diagnosed and confrmed positive for COVID-19 in the frst 6 months of the pandemic entering Indonesia, located in Madiun Regency, East Java Province, Indonesia. We conducted face-toface semi-structured interviews with health protocols and analyzed using the 6-step of Interpretative Phenomenological Analysis (IPA) method. Results: Three themed-fndings illustrate patients’ psychosocial experiences before being diagnosed: 1) cooperative behavior during the pandemic (with sub themes: recognizing symptoms and looking for medical help); 2) Navigating feelings when frst received a diagnosis (with sub themes: being worried about the diagnosis, suspecting infection based on exposure history, and acknowledging the existence of COVID-19); and 3) Early psychosocial responses (with sub-themes: psychological response, cognitive response,behavioral response, family responses, and social response). Conclusion: Exploring the experiences of patients with confrmed COVID-19 before and undergoing the isolation period can provide opportunities to improve the quality of physical and psychological services starting from prevention and assistance when receiving a diagnosis so as not to experience a worsening of the condition during treatment. Recommendations are for further study about COVID-19 survivors among children and adolescents who have been treated in the intensive care unit.